Norman Dott (1897–1973) and medical illustration: the importance of art to neurosurgery. (4th July 2021) - Hayes, Elspeth N.; Williams, Louise A.; Alberti, Sam; Demetriades, Andreas K.
Abstract: Anatomical information and pathologies have been conveyed through the medium of medical illustrations for centuries. In the formative years of British neurosurgery, Professor Norman Dott (1897–1973) utilised medical illustrations as a means of documenting neurosurgical advances and conveying pathological-anatomical correlation. He commissioned a vast number of medical illustrations over the course of his career, ultimately producing a diverse collection of items, most of which is cared for by Lothian Health Services Archive (LHSA), Edinburgh, Scotland. In this study, the original material from Dott's personal collection was audited. Of 172 stand-alone drawings, 84 were categorised and analysed. The findings are a reflection of Dott's expertise as an academic and a surgeon. Spanning the years 1925–1968, a wide range of pathologies and procedures are depicted including intracranial aneurysms and their ligation, an area in which Dott was renowned for pioneering surgical advances. The collection stands as a testament to Dott's emphasis upon medical illustration to communicate the intricacies and complexities of his field, providing valuable insight into clinical and surgical practice in neurosurgery when the specialty was in its juvenescence. In order to illuminate the connections between biography and specialism that generated an extraordinary visual archive, this study considers the early life and work of Norman Dott and the influence of Harvey Cushing on Dott's prioritisation of visual documentation of surgical practice. It explores the impact of German–American medical artist Max Brödel on the UK, and especially on the artists employed by Dott, before presenting a short review of the medical illustrations they created.